BIRTH CONTROL PILLS AND POSSIBLE INFLUENCES ON THE FETUS - Alina Mihaela Calin; Gabi Topor; Nicolae Sarbu; Iulia Alecsandra Salcianu; Ana Magdalena Bratu; Minodora Campanu (Banu); Simona Parvu; Norin Forna; Iulian Catalin Bratu (Romanian Society of Oral Rehabilitation, 2024)
Birth control pills are widely used around the world for birth control and prevention of unwanted pregnancy. However, there are concerns about their safety during pregnancy and possible effects on the fetus. This article aims to examine in depth the current evidence on the impact of birth control on the foetus. By analysing the mechanism of action of birth control pills, relevant clinical trials and associated potential complications, the risks and safety of contraceptive use during pregnancy are explored. The different types of contraceptives and the specific risks associated with each are discussed, providing recommendations for women who use birth control and become or become pregnant. Through this literature review, the aim is to provide a clearer understanding of this topic and to provide practical guidance for healthcare professionals and women in this situation. Further investigation into the mechanisms of action of birth control pills during pregnancy and how they may influence fetal development could provide useful information for managing and counseling women who are pregnant or planning to become pregnant.